IMPLEMENTASI PRINSIP NEGARA HUKUM DALAM PENEGAKAN HAM DI INDONESIA: STUDI TERHADAP PUTUSAN MAHKAMAH KONSTITUSI - Hidayah, Syaiful; Frinaldi, Aldri; Rembrandt, Rembrandt; Lanin, Dasman; Umar, Genius (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2025)
The implementation of the rule of law principle in the enforcement of Human Rights (HR) in Indonesia has become a major focus in constitutional governance. This study aims to analyze the role of the Constitutional Court (MK) in implementing the rule of law principle through rulings that focus on human rights protection. By using a normative juridical approach and analyzing MK rulings, this study reveals that although MK has successfully upheld human rights through judicial review, significant challenges remain, especially in terms of the implementation of these decisions in practice. Limited legal culture and political commitment are the main obstacles to the successful and comprehensive application of the rule of law principle. Therefore, strengthening synergy among state institutions and improving legal literacy for the public are essential to achieving the rule of law principle that upholds human rights.